Ecclesiastes - Enns, Peter 1961- (Grand Rapids, Mich. Cambridge, U.K. William B. Eerdmans Publishing Company, 2011)
In this expert commentary on Ecclesiastes, Peter Enns neither disregards nor attempts to resolve the book's many theological tensions and ambiguities. Rather, he shows how these form the backdrop against which the author struggles to show readers the proper path forward in their journeys of faith -- remaining true to the tradition to "fear God and keep the commands" despite the apparent futility of human existence. --from publisher description
Formerly CIP Uk. - Includes bibliographical references
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Commentaries; Bible -- O.T -- Ecclesiastes -- Commentaries; Kommentar